2003
DOI: 10.1111/1540-6261.00576
|View full text |Cite
|
Sign up to set email alerts
|

Momentum and Reversals in Equity‐Index Returns During Periods of Abnormal Turnover and Return Dispersion

Abstract: We document new patterns in the dynamics between stock returns and trading volume. Speci¢cally, we ¢nd substantial momentum (reversals) in consecutive weekly returns when the latter week has unexpectedly high (low) turnover. This pattern is evident in equity indices, index futures, and individual stocks. Similarly, we also ¢nd that the autocorrelation in equity-index returns is increasing with the unexpected dispersion across the latter week's ¢rm-level returns. Weeks with extreme turnover and dispersion shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…Some researchers attribute momentum to investors' overreaction or underreaction to firm-specific news, 1 while others use rational riskreturn theories to interpret momentum. Some recent studies on risk-based explanations on momentum returns include Connolly and Stivers (2003), Grundy and Martin (2001), Chordia and Shivakumar (2002), Johnson (2002), Ahn et al (2003), and Moskowitz (2003). 2 Nevertheless, these studies do not reach a conclusive explanation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some researchers attribute momentum to investors' overreaction or underreaction to firm-specific news, 1 while others use rational riskreturn theories to interpret momentum. Some recent studies on risk-based explanations on momentum returns include Connolly and Stivers (2003), Grundy and Martin (2001), Chordia and Shivakumar (2002), Johnson (2002), Ahn et al (2003), and Moskowitz (2003). 2 Nevertheless, these studies do not reach a conclusive explanation.…”
Section: Introductionmentioning
confidence: 97%
“…Behavioral explanations on momentum returns include investors' underreaction to firm-specific news (Barberis et al 1998 andGrinblatt andHan 2005) or overreaction to firm-specific news (Daniel et al 1998, 2001, Hong and Stein 1999, and Barberis et al 2003. 2 Lee and Swaminathan (2000) and Connolly and Stivers (2003) suggest that industry past volume predicts future returns. Grundy and Martin (2001) and Jegadeesh and Titman (2001) find that cross-sectional differences in expected returns is not the dominant cause of momentum.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, higher trading volume is generally found to be accompanied by a drop in return autocorrelation. Recently, Connolly and Stivers (2003) evaluated the autocorrelation properties of stock returns in conjunction with abnormal turnover on a weekly basis. They found momentum in stock returns in the case of contemporaneous, abnormally high trading volume, while returns reverse direction in the case of abnormally low trading volume.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Christie and Huang (1994) find that return dispersion is associated with the business cycle; return dispersion is higher during economic recessions. Connolly and Stivers (2003) show that momentum (reversal) is positively (negatively) related to future return dispersion. Harvey (1997, 2000) document that a higher return dispersion tends to have a higher (lower) volatility level for developed (emerging) markets.…”
mentioning
confidence: 91%